Dietary Supplementation With Leucine or in Combination With Arginine Decreases Body Fat Weight and Alters Gut Microbiota Composition in Finishing Pigs - Hu, Chengjun; Li, Fengna; Duan, Yehui; Yin, Yulong; Kong, Xiangfeng (Frontiers in Microbiology, 2019)
Obesity was associated with change in gut microbiota composition and their metabolites. We investigated the effects of dietary supplementation with leucine (Leu) in combination with arginine (Arg) or glutamic acid (Glu) on body fat weight, composition of gut microbiota, and short-chain fatty acids (SCFAs) concentration in the colon. Forty-eight Duroc × Large White × Landrace pigs with an initial body weight of 77.08 ± 1.29 kg were randomly assigned to one of the four groups (12 pigs per group). The pigs in the control group were fed a basal diet supplemented with 2.05% alanine (isonitrogenous control, BD group), and those in the three experimental groups were fed a basal diet supplemented with 1.00% Leu + 1.37% alanine (Leu group), 1.00% Leu + 1.00% Arg (Leu_Arg group), or 1.00% Leu + 1.00% Glu (Leu_Glu group). We found that dietary supplementation with Leu alone or in combination with Arg decreased (p < 0.05) body fat weight, and increased (p < 0.05) colonic propionate and butyrate concentrations compared to the BD group. The mRNA expression levels of genes related to lipolysis increased (p < 0.05) in the Leu or Leu_Arg group compared to the BD group. Negative relationships (p < 0.05) were observed between body fat weight, colonic propionate, and butyrate concentrations. Compared to the BD group, the abundance of Actinobacteria was higher (p < 0.05) in the Leu group, and that of Clostridium_sensu_stricto_1, Terrisporobacter, and Escherichia-Shigella were higher in the Leu_Arg group. The abundance of Deinococcus-Thermus was negatively correlated (p < 0.05) with body fat weight, and was positively correlated (p < 0.05) with butyrate, isovalerate, propionate, and isobutyrate concentrations, and that of Cyanobacteria was positively correlated (p < 0.05) with butyrate, propionate, and isobutyrate concentrations. In conclusion, these findings suggest that decreased body fat weight in pigs can be induced by Leu supplementation alone or in combination with Arg and is associated with increased colonic butyrate and propionate concentrations. This provides new insights for potential therapy for obesity.